PENERAPAN MODEL PBL UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS BERITA SISWA SMP NEGERI 6 PONTIANAK - Maulina, Natasya; Heryana, Nanang; Lasmono, Djon (Universitas Tanjungpura, 2024)
This study has a goal, namely to improve the skills of writing news texts for class VII students of SMP Negeri 6 Pontianak. The method used is a class action method which is described as it is with a form of research that is descriptive qualitative. The subjects of this study were students of class VII A, which consisted of 30 students. The data obtained is the result of the skills of writing news texts arranged by students by applying the PBL or problem-based learning model. The actions taken in this study were carried out in two cycles with two meetings per cycle. The results of the skills of writing news text using the PBL model with newspaper media in the first cycle were 76% and the average score for writing news text skills using the PBL model with YouTube media in cycle II was 83.4%. The acquisition results increased by 7.4, while the cycle I activities obtained an average score of 76%. This is show that the Problem Based Learning model can improve the news text writing skills of class VII A student of SMP Negeri 6 Pontianak it a relatively high everage.